Vericiguat improves cardiac remodelling and function in rats with doxorubicin‐induced cardiomyopathy - Wen Chen; Ying Wu; Wei Li; Meiyan Song; Kaizu Xu; Meifang Wu; Liming Lin (ESC Heart Failure)
Abstract Purpose Vericiguat, a soluble guanylate cyclase (sGC) stimulator, has been demonstrated effective in improving prognosis of patients with heart failure with reduced ejection fraction. However, there are limited data concerning the effect of vericiguat in patients with doxorubicin (DOX)‐induced cardiomyopathy (DIC). In this study, we investigated the effects of vericiguat on cardiac structure and function in rats with DIC as well as their potential mechanisms of action. Methods DIC rats were established by intraperitoneal injection of DOX (1 mg/kg) twice a week for 6 weeks, followed by intragastric administration of vericiguat 1 mg/kg/day or an equal volume of normal saline for 8 weeks. Cardiac histology and function, circulating levels of amino‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), nitric oxide (NO), and oxidative indices, as well as myocardial cyclic guanosine monophosphate (cGMP)‐protein kinase G (PKG) signalling, oxidative and apoptosis‐associated protein were measured. Results Compared with the control group, rats treated with DOX exhibited significantly increased heart size, reduced systolic function and elevated plasma levels of NT‐proBNP. Histological findings revealed myocardial cell atrophy, fibrosis and apoptosis. Vericiguat treatment effectively reversed DOX‐induced cardiac remodelling and improved systolic function. Mechanistically, Vericiguat attenuated the inhibitory effects of DOX on the myocardial cGMP‐PKG axis and nuclear factor erythroid 2‐related factor 2 (Nrf2) protein, thereby alleviating oxidative stress and apoptosis. Conclusions Vericiguat improved cardiac remodelling and contractile function in rats with DIC through upregulation of cGMP‐PKG signalling and inhibition of oxidative stress and myocardial apoptosis.